Can "Focused Deterrence" Produce More Effective Ethics Codes? An Experimental Study. Issue 1 (January 2022) - Rorie, Melissa; West, Matthew
The current study draws from the literature on "direct deterrence" programs as a framework for preventing corporate crime. Direct deterrence programs focus on reducing crime by communicating the likelihood and severity of sanctions to potential offenders. We believe a similar strategy may be useful when designing ethics codes. Ethics codes are the most commonly applied aspect of corporate internal compliance programs, yet evidence supporting their effectiveness is mixed and rigorous evaluation of their impact rare. Here, we employed an experimental design to examine how the content of ethics codes impact ethical decisions. Results suggest that the presence of an ethics code can increase compliance, but that supervisors also play a critical role. Implications for research and internal compliance programs are discussed.